Deciphering Cassandra as a Radical Feminist in Promising Young Woman (2020) - Syarifa, Alika Rahma; Trisnawati, Ririn Kurnia; Agustina, Mia Fitria (LPPM Universitas Advent Indonesia, 2023)
Every woman has different nature either being strong or being weak. Not all women have a lucky fate; in fact, many of them become the victims of men. Of the many cases of violence and sexual harassment in the world, women mostly become victims, especially in cases of sexual acts without consent. In Promising Young Woman (2020), these issues are conveyed very well. Its main character, Cassandra, carries out a mission that targets men who try to take advantage of drunken women to become deterrent and frightened. The purpose of this qualitative study on the film is aimed to discuss the behavior of radical feminism living in the character of Cassandra. Cassandra reflects a radical feminist attitude in order to achieve revenge and conveys a message about women's rights to obtain justice. Radical feminism occurs based on three key issues namely sexual objectification of women, rape, and patriarchy. The result shows that Cassandra can fully be claimed as a radical feminist because there are several characteristics of radical feminism that match the nature and behavior of Cassandra in the film, which are opposing sexual objectification of women, opposing sexism, and toxic masculinity, lastly patriarchy.